ANALISIS KORELASI SIFAT BIOLOGI DAN KIMIA TANAH PADA BERBAGAI TIPE PENGGUNAAN LAHAN DI KABUPATEN BOGOR - Indri Hapsari Fitriyani; Fahrizal Hazra; Dewi Rosita (Jurnal Tanah dan Sumberdaya Lahan, 2023)
Land use in Bogor Regency has diverse vegetation and different soil characteristics. Soil characteristics have an influence on land management. Improper land management has led to a decrease in microbial populations, biodiversity and a decline in soil quality and fertility. Soil fertility is produced by the interaction of the physical, chemical, and biological properties of the soil. This study aims to determine the correlation of soil biological and chemical properties in several different types of land use in Bogor Regency. Soil sampling was carried out using the purposive random sampling method with five replicates. Soil samples were taken at a depth of 0-20 cm by ±1 kg. The research site includes eight land uses namely bamboo gardens, sengon gardens, lamtorogung gardens, and dragon fruit orchards. The results of the analysis showed that the dragon fruit field had an acid pH with very high organic C and total N levels with the highest fungal population of 2.27 x 105 CFU g-1. Meanwhile, bamboo fields with an acid pH also have a medium organic C content and low total N with the lowest total fungi population of 0.37 x 105 CFU g-1. Azotobacter populations and respiration values had the highest correlation with the total P content of the soil. The correlation value of the total population of fungi was the highest, with a total N levels of 0.427.